Natural gas : a basic handbook - Speight, James G. (Cambridge, MA, United States : Gulf Professional Publishing, 2019)
Natural Gas: A Basic Handbook, Second Edition provides the reader with a quick and accessible introduction to a fuel source/industry that is transforming the energy sector. Written at an introductory level, but still appropriate for engineers and other technical readers, this book provides an overview of natural gas as a fuel source, including its origins, properties and composition. Discussions include the production of natural gas from traditional and unconventional sources, the downstream aspects of the natural gas industry. including processing, storage, and transportation, and environmental issues and emission controls strategies. This book presents an ideal resource on the topic for engineers new to natural gas, for advisors and consultants in the natural gas industry, and for technical readers interested in learning more about this clean burning fuel source and how it is shaping the energy industry
includes bibliographical references and index
Includes bibliographical references and index
Keywords: Natural gas